Characteristics and outcomes of adolescents living with HIV transitioning to adulthood in different health care models across Southern Africa - Tsondai, Priscilla (Department of Public Health and Family Medicine, 2026)
Adolescents and young people constitute an increasing proportion of the global population living with HIV, reflecting the shift in the burden of paediatric HIV towards older age groups. The recognition of an emerging cohort of young individuals living with HIV is indisputable. Nevertheless, there exists a notable dearth of understanding concerning the identification and timing of their transition to adulthood within the sub-Saharan Africa context. Although progress has been made in research on the transition of adolescents and youth living with HIV (AYLH) into adult care within developed nations, the field remains in its nascent stages in low- and middle-income countries (LMICs), where the majority of this population resides. Particularly concerning is the lack of information regarding the outcomes experienced by AYLH as they progress into adulthood in settings where the transition to adulthood necessitates the assumption of greater responsibility for their healthcare, without the physical transfer of care from paediatric or adolescent clinics to specialized adult HIV clinics, as may be the prevalent scenario within sub-Saharan Africa. To effectively evaluate and compare transition outcomes, it is imperative to establish optimal measurement approaches and implement comprehensive data collection practices across diverse settings. National programs and research cohorts in LMICs have made limited efforts to document the transition experience and associated factors. Moreover, the absence of a standardized approach to measure and compare transition-related processes and outcomes across different settings severely impedes the surveillance of outcomes specific to transitioning adolescents. Furthermore, most studies that have scrutinized transition-related outcomes have predominantly focused on post-transition outcomes, paying limited attention to the engagement in care among transitioning youth during the pre-transition period. Given that transitioning adolescents often undergo a protracted period of HIV care and ART prior to the formal transition, it is necessary to establish a comprehensive "adolescent transition cascade" that assesses outcomes both preceding and succeeding this critical phase. Therefore, there is a need for comprehensive longitudinal studies that track AYLH. Analyses that combine rigorous quantitative data collection, such as linked medical records with qualitative techniques such as in-depth interviews, will provide a more nuanced understanding of the complex transition process. Encouraging collaboration and networking among researchers across different countries could foster development of standardized measurement tools that accurately assess transition-related processes and outcomes. This will enhance the comparability of data across various studies and settings, facilitating a more comprehensive analysis of the factors that influence successful transitions. Aim and objectives: This thesis aims to provide a comprehensive description of the characteristics and outcomes of adolescents living with HIV across Southern Africa throughout the adolescent transition cascade. Additionally, it aims to identify the factors that contribute to these outcomes. Given the limited availability of standardized measurement tools that accurately assess transition-related processes and outcomes in resource-limited settings, this thesis also endeavours to develop and pilot a widely applicable and accessible data collection and management platform that will facilitate the measurement of transition processes and outcomes in adolescent HIV care.